Sistem Informasi Pemantauan Retribusi Pada Menara Telekomunikasi - Pratiwi; Afdal Suganda; Ririt Dwiputri Permatasari; Ismail Yusuf Panessai (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2019)
Tekomunikasi adalah salah satu faktor penting dan strategis dalam mendukung dan meningkatkan daya saing ekonomi suatu negara. Telekomunikasi juga berperan dalam peningkatan pendidikan dan peningkatan hubungan antar negara. Pembangunan menara telekomunikasi diperlukan untuk memperhatikan estetika lingkungan, tata ruang dan wilayah serta orang-orang keselamatan dan keamanan yang berada di sekitar menara telekomunikasi. Peran pemerintah kota untuk mengatur penyelenggaraan perizinan, khususnya terkait dengan perizinan menara telekomunikasi sangat penting agar pendirian menara telekomunikasi tidak sembarangan dan merugikan banyak pihak. Dengan terjadinya masalah-masalah ini, kita membutuhkan aplikasi yang dapat membantu pemerintah kota dalam mengelola pemantauan dan retribusi data oleh menara telekomunikasi. Information System for Information Levy Monitoring On Telecommunication Towers Abstract: Telecommunications is one of the important and strategic factor in supporting and enhancing the competitiveness of a nation's economy. Telecommunications also play a role in the improvement of education and improvement of relations between nations. Telecommunications tower construction is required to pay attention to the aesthetics of the environment, spatial and regions as well as safety and security people residing around the telecommunications tower. The role of the city government to regulate the operation of licensing, particularly related to the licensing of telecommunications tower is very important for the erection of the tower telekominikasi not arbitrary and detrimental to many parties. With the occurrence of these problems, we need an application that can help the city government in managing data monitoring and levies by the telecommunications tower. Keywords: License, Telecommunication Tower, Client-Server.